CLAHR : Colonial Latin American Historical Review (Alburquerque University of New México)
Signatura: 93/047
Existencia : 1992- 1(1); 1993- 2(2-4); 1994-3(1-4); 1995- 4(1-4); 1996- 5(1-4); 1996- 5(1-4); 1997- 6(1-4); 1998- 7(1-4); 1999- 8(1-4)
Keywords: Historia; America Latina